Post-transplant cyclophosphamide in haploidentical stem cell transplantation: evaluating the impact of transplant conditioning intensity - Pizzano, Umberto; Piemontese, Simona; Facchin, Gabriele; Greco, Raffaella; Battista, Marta Lisa; Peccatori, Jacopo; Fanin, Renato; Ciceri, Fabio; Patriarca, Francesca; Lupo-Stanghellini, Maria Teresa (Frontiers in Immunology, 2025)
BackgroundThe introduction of posttransplant cyclophosphamide (PTCy) is one of the major achievements in the field of haploidentical stem cell transplantation (haplo-HCT). The transplant conditioning intensity (TCI) score is a refined classification of conditioning regimens that assigns weight scores to conditioning regimen components. The aim of our analysis was twofold: to assess the effect on transplant outcomes of combining PTCy with calcineurin inhibitor + mycophenolate mofetil (MMF) instead of mTOR inhibitor + MMF for GvHD prophylaxis, and to assess the effect of stratification by conditioning intensity in the setting of haplo-HCT.MethodsThis study was conducted in adult patients who underwent haplo-HCT at the University Hospital of Udine (UUH) or Ospedale San Raffaele (OSR) between January 2014 and December 2021. Patients received PTCy plus CsA-MMF at UUH and sirolimus-MMF at OSR. Conditioning intensity was defined by the TCI score. All data were collected prospectively.ResultsA total of 216 haplo-HCTs were performed, 81 at UUH and 135 at OSR. Notably, none of the patients at UUH received a high TCI score regimen compared to 72 (53.3%) at OSR. Our results show overlapping survival outcomes (OS, NRM, DFS, GRFS, and RI) within the two platforms. We observed a higher incidence of cGvHD within the sirolimus/MMF + PTCy platform, and high TCI was found to be the only risk factor for a higher incidence of grades III–IV aGvHD in univariate analysis.ConclusionOur results suggest that TCI may reveal the role of chemoradiotherapy in promoting conditions that may contribute to the occurrence of GvHD. The impact of moderate/severe cGvHD on quality of life must challenge our efforts to further optimise prophylactic strategies.